A study on women's right: women's employment and how it affects women's wage rates in private sector / Sofia Asyikin Mohd Kamil … [et al.] - Mohd Kamil, Sofia Asyikin; Mohd Sanusi, Idyvino Saha; Roslan, Muhammad Hassanuddin; Yusdi Madeonus, Elyna Nabila Madeonus (Faculty of Law, 2013)
In Malaysia, female labour force participation rate is very much lower than that of males, even though they are equally educated. It is commonly observed that women are always less preferable by employers because they are perceived to have less skilled and immobile as compared to men. For women who successfully enter the labour market, they often receive lower wages than their male counterparts do, partly due to discriminatory practices. This paper attempts to examine gender wage gap and legal regulations protecting it in Malaysia for private sector. The analysis of this paper will consist of two parts. The first part will identify the gender wage gap in Malaysia and its relation to employment of women in private sector and secondly, the legal regulations protecting the said issue.